2006
DOI: 10.1111/j.1469-7998.2006.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Home range, habitat choice and activity of stoats (Mustela erminea) in a subarctic area

Abstract: We monitored the home ranges, habitat use and activity of stoats Mustela erminea in north-west Finnish Lapland with radio-tracking in years 1998 and 1999, and found a dominance hierarchy in habitat use between and within sexes. Altogether, eight female and seven male stoats were caught and radio-tracked. Males and females differed from each other both in the size of their home ranges and in habitats. Mature females live in areas where the abundance of the preferred Microtus prey is the highest. Dominant males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Stoats respond mainly numerically with an approximately nine-month lag to changes in the density of their main prey, voles (Korpimäki et al 1991). After a crash in the vole population, stoats increase their mobility and expand their ranges from main habitats (grasslands and cultivated fields) to forests (Klemola et al 1999;Hellstedt and Henttonen 2006), where the probability of encountering grouse broods increases. We also found a positive correlation between the predation index of grouse hens and the ratio of the abundance index of stoats to the bank vole index.…”
Section: Discussionmentioning
confidence: 99%
“…Stoats respond mainly numerically with an approximately nine-month lag to changes in the density of their main prey, voles (Korpimäki et al 1991). After a crash in the vole population, stoats increase their mobility and expand their ranges from main habitats (grasslands and cultivated fields) to forests (Klemola et al 1999;Hellstedt and Henttonen 2006), where the probability of encountering grouse broods increases. We also found a positive correlation between the predation index of grouse hens and the ratio of the abundance index of stoats to the bank vole index.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported clear ecological divergence in species that show little differences in morphology (e.g. Gray & Hamer, 2001; Lewis et al ., 2002; Hellstedt & Henttonen, 2006), lending further support to the notion that the directly linking of morphology with ecology may need to be reassessed.…”
mentioning
confidence: 81%
“…Durell, Gosscustard & Caldow, 1993; Braña, 1996; Pearson, Shine & How, 2002; Page, McKenzie & Goldsworthy, 2005; Herrel et al ., 2006), microhabitat use (e.g. Vidal, Ortiz & Labra, 2002; Both, Edelaar & Renema, 2003; Wolf, Kauermann & Trillmich, 2005; Hellstedt & Henttonen, 2006), and thermal ecology (e.g. Van Damme, Bauwens & Verheyen, 1986; Perez‐Mellado & Dela Riva, 1993; Brown & Weatherhead, 2000).…”
mentioning
confidence: 99%
“…Thereafter, African elephants exhibit pronounced sexual dimorphism in both size and behaviour (Lee & Moss, ). The forage selection hypothesis predicts that these differences may lead to segregation of the sexes by virtue of their size dimorphism (Berteaux, ; Mysterud, ; Hellstedt & Henttonen, ; Shannon et al ., ). Being smaller, adult females are generally more selective in the resources they use (Shannon et al ., ; Woolley, Page & Slotow, ), whereas adult males can tolerate a wider range of forage quality.…”
Section: Introductionmentioning
confidence: 99%